ANALISIS SEMIOTIKA BILLBOARD SETENGAH JADI DARI KITKAT BERJUDUL “BREAK” OLEH JWT LONDON - Fernando, Vito; muhammad adi sukma nalendra (Puslitabmas Batam Tourism Polytecnic, 2024)
Billboards or advertising billboards are advertising media placed on large boards positioned strategically. They usually contain visuals or messages that attract attention to promote products, services, or specific messages to the audience. One of the attention-grabbing billboards is the KitKat brand advertisement titled